EFEKTIVITAS COGNITIVE BEHAVIOR THERAPY (CBT) UNTUK MENINGKATKAN KUALITAS TIDUR PENDERITA GEJALA INSOMNIA USIA DEWASA AWAL - Hapsari, Artani; Kurniawan, Afif (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Early adulthood becomes a period which cognitive and physical development functions optimally so that it affect young adult to have new activities and experiences that are vulnerable to an unhealthy lifestyle, such as smoking, alcohol consumption, and excessive caffeine consumption. The more daily activity they have, the higher they become depressed that impacts on irregular sleep patterns, decreased sleep quality, and experience symptoms of insomnia. The purpose of this study was to examine the effectiveness of Cognitive Behavior Therapy (CBT) to improve sleep quality in patients with insomnia symptoms in early adulthood. The study used an experimental research method with one group pre-test post-test experimental design, and took samples of 4 people with age range between 20-25 years. The Pittsburgh Sleep Quality Index (PSQI) was used as measurement tool and furthermore writer used Wilcoxon Signed-Rank Test to analyze the data. The results showed a significant sleep quality difference of 4 subjects prior and after CBT. CBT’s components such as stimulus control, sleep restriction, sleep hygiene education, and cognitive therapy believed to affects sleep quality in this study. Other than that, internal factors like motivation and obedient towards therapy and also external factors like support from fellow subjects or family members become factors which affects changes in subjects’ condition.